Final overall survival results of a randomized trial comparing bortezomib plus pegylated liposomal doxorubicin with bortezomib alone in patients with relapsed or refractory multiple myeloma. Issue 13 (18th May 2016) - Orlowski, Robert Z.; Nagler, Arnon; Sonneveld, Pieter; Bladé, Joan; Hajek, Roman; Spencer, Andrew; Robak, Tadeusz; Dmoszynska, Anna; Horvath, Noemi; Spicka, Ivan; Sutherland, Heather J.; Suvorov, Alexander N.; et al.
Abstract : BACKGROUND: Previous results from an interim analysis of an open‐label, randomized, phase 3 study demonstrated that bortezomib combined with pegylated liposomal doxorubicin (PLD) was superior to bortezomib monotherapy in patients with relapsed/refractory multiple myeloma who had previously received one or more lines of therapy. Protocol‐defined final survival data from that study are provided here. METHODS: Patients were randomized (1:1) to receive either bortezomib alone (1.3 mg/m 2 intravenously on days 1, 4, 8, and 11 of every 21‐day cycle) or bortezomib‐PLD (bortezomib plus PLD 30 mg/m 2 intravenously on day 4). The primary endpoint was the time to progression. Secondary efficacy endpoints included overall survival (OS), progression‐free survival, and the overall response rate. RESULTS: In total, 646 patients (bortezomib‐PLD, n = 324; bortezomib alone, n = 322) were randomized between December, 2004, and March, 2006. On the clinical cutoff date (May 16, 2014) for the final survival analysis, at a median follow‐up of 103 months, 79% of patients had died (bortezomib‐PLD group: 253 of 324 patients; 78%; bortezomib alone group: 257 of 322 patients; 80%). The median OS in the bortezomib‐PLD group was 33 months (95% confidence interval [CI], 28.9‐37.1) versus 30.8 months (95% CI, 25.2‐36.5) in the bortezomib alone group (hazard ratio, 1.047; 95% CI, 0.879‐1.246; P = .6068). Salvage therapies included conventional and novel drugs, which were well balanced between the two treatment groups. CONCLUSIONS: Despite inducing a superior time to progression, long‐term follow‐up revealed that PLD‐bortezomib did not improve OS compared with bortezomib alone in patients with relapsed/refractory multiple myeloma. The inability to sustain the early observed survival advantage may have been caused by the effects of subsequent lines of therapy, and underscores the need for long‐term follow‐up of phase 3 trials while recognizing the challenge of having adequate power to detect long‐term differences in OS. Cancer 2016;122:2050–6 . © 2016 American Cancer Society . Abstract : Despite the superior time to progression observed and the early trend in favor of overall survival with bortezomib‐pegylated liposomal doxorubicin combination therapy, long‐term follow‐up reveals that treatment with the bortezomib‐pegylated liposomal doxorubicin combination does not improve overall survival compared with bortezomib monotherapy in patients with relapsed or refractory multiple myeloma. See also pages 1971‐3.